Impacts of Pta-AckA pathway on CPS biosynthesis and type 3 fimbriae expression in Klebsiella pneumoniae - Tien-Huang Lin; Chen-Yu Wang; Chien-Chen Wu; Ching-Ting Lin (Journal of Microbiology, Immunology and Infection)
Background: Klebsiella pneumoniae is a Gram-negative bacterium that can cause infections, especially in individuals with diabetes. Recently, more hypervirulent strains have emerged, posing a threat even to healthy individuals. Understanding how K. pneumoniae regulates its virulence factors is crucial. Acetyl-phosphate (AcP) is essential for bacterial metabolism and can affect virulence factor expression. However, the role of the Pta-AckA pathway, which regulates AcP levels, in K. pneumoniae pathogenesis remains unclear. Methods: Deletion mutants lacking the pta and ackA, involved in AcP production and hydrolysis, were generated in K. pneumoniae CG43S3. Their effects on AcP levels, the patterns of global acetylated protein, capsular polysaccharide (CPS) amount, serum resistance, type 3 fimbriae expression, biofilm formation, and virulence in G. mellonella larva were assessed. Results: Deletion of ackA in K. pneumoniae CG43S3 led to AcP accumulation, while pta deletion abolished AcP synthesis when grown in TB7+1 % glucose. This pathway influenced global protein acetylation, with pta deletion decreasing acetylation and ackA deletion increasing it. Additionally, pta deletion decreased the CPS amount, serum resistance, and type 3 fimbriae expression, while ackA deletion increased these factors. Furthermore, deleting pta and ackA attenuated the infected larva's virulence and death rate. Conclusion: Our findings highlight the critical role of the Pta-AckA pathway in K. pneumoniae pathogenesis. This pathway regulates AcP levels, global protein acetylation, CPS production, serum resistance, and type 3 fimbriae expression, ultimately impacting virulence. The information provides insights into potential therapeutic targets for combating K. pneumoniae infection.